2017
DOI: 10.1186/s13071-017-2174-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and phylogeny of Wolbachia strains in wild mosquito populations in Sri Lanka

Abstract: Background Wolbachia are a group of maternally inherited intracellular bacteria known to be widespread among arthropods. Infections with Wolbachia cause declines of host populations, and also induce host resistance to a wide range of pathogens. Over the past few decades, researchers were curious to use Wolbachia as a biological tool to control mosquito vectors. During the present study, assessment of the prevalence of Wolbachia infections among wild mosquito populations in Sri Lanka where mosquito-borne diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
44
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 46 publications
(72 reference statements)
14
44
1
1
Order By: Relevance
“…Interestingly in Sri Lanka, 3/3 (100%) of Ma. uniformis individuals amplified the wsp gene 52 but in our study all seven individuals failed to amplify wsp. Ma.…”
Section: Discussioncontrasting
confidence: 56%
“…Interestingly in Sri Lanka, 3/3 (100%) of Ma. uniformis individuals amplified the wsp gene 52 but in our study all seven individuals failed to amplify wsp. Ma.…”
Section: Discussioncontrasting
confidence: 56%
“…gambiae . Previous studies had reported no observed natural Wolbachia infection in this mosquito vector 26-31 ; however, the endosymbiont was successfully detected in An. gambiae from Burkina Faso, West Africa using an optimized wsp protocol 32,33 .…”
Section: Discussionmentioning
confidence: 80%
“…With the recognition of about 65% of known insects to be naturally infected with Wolbachia including those mosquito species from the genera of Aedes, Culex, Mansonia , major mosquito vectors of diseases such as Ae. aegypti and Anopheline mosquitoes were reported not to possess this endosymbiont 26-31 . It led to the belief that the presence of Wolbachia endosymbiont could be the reason why many of the mosquito species are considered to be weak vectors 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The genus Asaia, first discovered in plant nectar, is an excellent candidate [166]; it is localized in many organs of mosquitoes, and can disperse inside the mosquito body through the haemolymph [165,167]. Its distribution in the mosquito population is made possible through several mechanisms (co-feeding, sexual mating, paternal, maternal, and horizontal transmission) [168][169][170]. Asaia bacteria may be genetically modified in order to be recolonised in a new host, resulting in spread within wild populations [166].…”
Section: Asaiamentioning
confidence: 99%